Toward sustainability in zeolite manufacturing: An industry perspective - Parvulescu, Andrei-Nicolae; Maurer, Stefan (Frontiers in Chemistry, 2022)
Conventional zeolite manufacturing processes are highly energy-intensive and come along with a significant carbon dioxide footprint. Here, we discuss the main energy consumers and potential alternatives toward a more sustainable production of zeolites: from simple optimization efforts on existing unit operations to new and novel manufacturing concepts such as the continuous crystallization and solidothermal route toward zeolites and their industrial applicability. These efforts contribute to the global effort into transitioning manufacturing of chemicals and catalysts to a net-zero environment by cutting greenhouse gas emissions to as close to zero as possible.